Rancang Bangun Sepeda Listrik Tenaga Hybrid - Istiqo, Qabul; Hadikusuma, Mohd. Ilyas; Saufa, Nanda Rusyda (Jurusan Teknik Elektro Politeknik Negeri Pontianak, 2024)
Electric bicycles are bicycles that are battery powered and driven by a motor. Electric bicycles can utilize more than one energy source, namely generator energy and solar energy to supply the battery, which is called hybrid energy. Battery charging is limited when it is full to prevent overcharging. Battery charging can be done using several methods, one of which is the Constant Voltage (CV) method. The stage for synchronizing hybrid energy sources is to condition the voltage of both hybrid sources so that the same value is achieved. Conditioning over charge uses an auto cut-off circuit which can cut off the source current if the battery is full, indicated by a Light Emitting Diode (LED). Research shows that battery charging by relying on a boost converter to synchronize the two sources can work very well. The boost converter voltage does not accumulate because both boost converters are installed in parallel. The auto cut-off circuit can prevent overcharging the battery by utilizing a zener diode and relay.